2020
DOI: 10.1007/s00299-020-02554-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic re-assessment of the transposable element landscape of the potato genome

Abstract: Transposable elements (TEs) are DNA sequences with the ability to auto-replicate and move throughout the host genome. TEs are major drivers in stress response and genome evolution. Given their significance, the development of clear and efficient TE annotation pipelines has become essential for many species. The latest de novo TE discovery tools, along with available TEs from Repbase and sRNA-seq data, allowed us to perform a reliable potato TEs detection, classification and annotation through an open -source a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 74 publications
3
12
0
Order By: Relevance
“…A percentage not too far from our larger genomes, where in Puno it was 42.84% and in Cusco it was 41.06%. However, in the study by Zavallo D. et al (2020) found a TEs content of 18%, which represents half of the genomic coverage according to the data presented by Mehra M. et al (2015) and ours.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A percentage not too far from our larger genomes, where in Puno it was 42.84% and in Cusco it was 41.06%. However, in the study by Zavallo D. et al (2020) found a TEs content of 18%, which represents half of the genomic coverage according to the data presented by Mehra M. et al (2015) and ours.…”
Section: Discussionsupporting
confidence: 53%
“…The distribution, quantity, and genome coverage of TEs vary greatly, particularly between plants and animals, where LTRs and non-LTRs (LINE and SINE) are the predominant type of TE, respectively (Chalopin et al 2015). The content of TEs is highly variable in plants and generally shows a positive correlation with genome size (Zavallo D. et al, 2020). For example, up to 85% of the maize genome or 70% of the Norway spruce genome (Nystedt et al 2013) has been annotated as transposons, including unclassified and other repeating components, while in the more compact genome of Arabidopsis thaliana the TEs content is only 21% (Ahmed et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to assess the landscape of the diverse TE subclasses, we performed circos ideograms [133] for the scaffolds larger than 10 Mbp (7 scaffolds) of each TE subclass as well as exon density as reference. The methodology was adapted from Zavallo et al 2020 [134].…”
Section: Methodsmentioning
confidence: 99%
“…Next, a BLAST search was performed against the wheat genome using the MITEs FASTA file as input. After filtering the results using the parameters described in Zavallo et al for transposable element annotation [15], 1.211.340 complete MITEs sequences were obtained.…”
Section: Identification and Annotation Of Mites In The Wheat Genomementioning
confidence: 99%
“…The results were subjected to a set of filters using a python scripts previously implemented [15] where elements shorter than 50 and larger than 1100 nucleotides were removed and a minimum distance between the start and end position of two different elements of five nucleotides is required to avoid duplicated hits. Also, a minimum percentage of identity between the query and the subject of 80% is required and the alignment length must be at least 80% the size of the query length.…”
Section: Mites Databasementioning
confidence: 99%